Pembangunan Portal Open Data untuk Mendukung Open Government dan Smart City (Studi Kasus: Pemerintah Daerah Kota Gorontalo) - Arip Mulyanto; Moh. Hidayat Koniyo; Rochmad M. Thohir Yassin (Jurnal Teknik, 2022)
Gorontalo City has a Smart City program that can help community activities, one of which is through easy access to data. However, currently stakeholders and the community have not been able to access these data easily, transparently, and accountably. The purpose of this research is to build an open government data portal application in Gorontalo City to make it easier for stakeholders and the public to access data in a transparent and accountable manner as an effort to create a more open government (Open Government), participatory, and innovative. The research method used in this research is the prototyping method, which is a software system development method where developers and users can interact with each other during the system creation process so that users can clearly define their needs to be translated by developers into application form. The prototyping method includes data collection for various sectors in each SKPD in Gorontalo City, data analysis, system prototype development which is an overview of the application being built, prototype evaluation, system coding namely the development of open data portal applications, system testing, and system evaluation by users. The results showed that the open data portal made it easier for stakeholders and the public to access data. With this open data portal application, the performance of the Gorontalo City government is more transparent and accountable in providing information for the people of Gorontalo City in particular and the public in general.